Left-Sided Patent Ductus Arteriosus in a Right-Sided Aortic Arch - Ming-Yen Ng; Paaladinesh Thavendiranathan; Andrew Michael Crean; Qin Li; Djeven Parameshvara Deva (Case Reports in Radiology)
We present a 31-year-old female with repaired tetralogy of Fallot (TOF) and right-sided aortic arch (RAA) with left-sided patent ductus arteriosus (PDA) originating from the left brachiocephalic artery. This is a rare finding but most common site for a PDA in TOF and a RAA. To the best of our knowledge, this is the first demonstration of this rare finding on MRI in the literature.